Pelatihan Implementasi Pendekatan Pembelajaran Mendalam bagi Guru Sekolah Dasar - Wahyudi, Achmad Basari Eko; Salimi, Moh.; Suhartono, Suhartono; Hidayah, Ratna; Surya, Anesa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
In this era of technological advancement, students face various challenges, both now and in the future, that are uncertain, uncertain, complex, ambiguous, and difficult to predict. These challenges can only be addressed through educational transformation to achieve quality and equitable education for all. Teachers should be able to facilitate each student according to their diverse learning needs. The objectives of this community service project are: 1) to describe the implementation of mentoring for the immersive learning approach in elementary schools, and 2) to describe the profile of teachers' abilities in implementing the immersive learning approach in elementary schools. This community service project was designed to provide training to principals and elementary school teachers in the Mirit District to design, implement, and evaluate the immersive learning approach. This community service project proceeded smoothly with various activities including: discussions on strengthening partnerships, training on developing immersive learning tools, immersive learning peerteaching practices, and discussions on evaluation and follow-up. Furthermore, teacher competency in immersive learning has developed, as seen from the immersive learning approach framework, namely understanding the eight dimensions of graduate profiles, learning principles, learning experiences, and the immersive learning framework.